ASSESSMENT OF ORGANISATIONAL CULTURE AND BEHAVIOUR OF RESEARCH, EXTENSION AND FARMERS ORGANISATIONS IN OYO STATE, NIGERIA (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study examined the organisational behaviour and culture of research, extension and farmers organisations in Oyo State, Nigeria. Structured interview schedule was used to collect data from 195 respondents (51 Research Officers, 69 Extension Personnel and 75 Farmers) selected through multistage sampling technique. Percentages, means and Linear Regression were used for data analysis. Results showed that the mean age, household size, work experience and annual income of the researchers were 43 years, 5 members, 10 years and N2,006,531.77 respectively; extension personnel were 42 years, 5 members, 12 years and N667,463.77 respectively while farmers were 43 years, 6 members, 18 years and N597,200.00 respectively. The organisational behaviours frequently exhibited were autocratic ( 3.69) for research, custodial (3.61) for extension and supportive and collegial (3.74) for farmers organisations respectively. The researchers ( 3.59) had good disposition of organisational culture while the extension personnel (4.24) and farmers ( 4.15) had very good disposition of organisational culture in their organisations respectively. Linear Regression showed that organisational culture of research organisation (β = 0.479; p<0.05), extension (β = 1.05; p<0.05) and farmers (β = 2.636; p<0.01) significantly influenced their respective organisational behaviour. The study concluded that organisational culture is an important contributor in determining the organisational behaviour of agricultural research, extension and farmers organisations in the study area. It was recommended that agricultural researchers, extension personnel and farmers should improve their organisational culture through collective capacity building and training programmes to enhance organisational behaviour in their respective organisations in the study area.